Investigating the Effectiveness of Socioemotional Competence Group Training on Social Adjustment, Alexithymia and Oppositional Defiant Disorder Symptoms among Adolescents - Mohamadpour, Fahimeh (International Journal of Applied Behavioral Sciences, 2024)
Background and Aim:The most important characteristics of oppositional defiant disorder are two sets of emotional and behavioral symptoms that manifest themselves in individual and social form. Therefore, the aim of this research was to investigate the effectiveness of social-emotional competence group training on social responsibility, alexithymia and severity of oppositional defiant disorder in adolescents. Materials and Methods:The current research was applied and semi-experimental with a pre-test-post-test and a control group. The research sample included 30 teenage girls with oppositional defiant disorder who were randomly divided into two groups of 15 people, experimental and control. The participants were tested on the scales of social adjustment, alexithymia and oppositional defiant disorder. Then, the treatment plan based on social-emotional competence group training was presented to the participants of the experimental group online in 9 two-hour sessions. Then, their scores were measured in the desired scales, after completing the treatment, and a three-month follow-up period. Descriptive statistics and covariance test were used to analyze the data. Results:The participants showed a clear improvement in the severity of symptoms in all three variables. So that the scores of alexithymia and oppositional defiant disorder in the experimental group after receiving the treatment, as well as after a three-month follow-up period, were significantly reduced and the social adjustment scores were also increased (p<0.001). Conclusion:In general, it can be concluded that social and emotional competence training can reduce the symptoms of oppositional defiant disorder in adolescents by correctly recognizing their own and others' emotions and helping to improve communication skills with others, and as a result, help to increase the adaptation of adolescents in society.